Better together: Simultaneous presentation of speech and gesture in math instruction supports generalization and retention. (August 2017) - Congdon, Eliza L.; Novack, Miriam A.; Brooks, Neon; Hemani-Lopez, Naureen; O'Keefe, Lucy; Goldin-Meadow, Susan
Abstract: When teachers gesture during instruction, children retain and generalize what they are taught (Goldin-Meadow, 2014). But why does gesture have such a powerful effect on learning? Previous research shows that children learn most from a math lesson when teachers present one problem-solving strategy in speech while simultaneously presenting a different, but complementary, strategy in gesture (Singer & Goldin-Meadow, 2005). One possibility is that gesture is powerful in this context because it presents information simultaneously with speech. Alternatively, gesture may be effective simply because it involves the body, in which case the timing of information presented in speech and gesture may be less important for learning. Here we find evidence for the importance of simultaneity: 3rd grade children retain and generalize what they learn from a math lesson better when given instruction containing simultaneous speech and gesture than when given instruction containing sequential speech and gesture. Interpreting these results in the context of theories of multimodal learning, we find that gesture capitalizes on its synchrony with speech to promote learning that lasts and can be generalized. Highlights: Gesturing during spoken instruction enhances learning, transfer and retention. It is unclear whether simultaneity between speech and gesture is key for learning. 3rd graders received a math lesson with simultaneous or sequential instruction. Speech with gesture promoted transfer and retention; speech then gesture did not. Simultaneity is an important ingredient in gesture's ability to facilitate learning.